Emergency First Aid Simulation for Drowning: Building Community Self-Reliance in the Sumber Jiput Tourist Area - Novita Ana Anggraini; Rahmania Ambarika; Elfi Quyumi Elfi; Byba Melda Suhita (Universitas STRADA Indonesia, 2026)
Drowning is an emergency that is a major cause of unintentional death, especially in children and communities living in water areas. The community's lack of knowledge and skills in recognizing risks and providing first aid in drowning incidents contributes to high morbidity and mortality rates. Drowning emergency education is an important promotive and preventive effort to increase community preparedness in facing such emergencies. This Community Service Program aims to assist the community in the Sumber Jiput water tourism area in practicing handling and providing first aid to drowning victims. The method used is by providing Health Education on handling and providing first aid to drowning victims. This Community Service Program was carried out at the Sumber Jiput water tourism area on Sunday, January 25, 2026, for 32 teenagers and Pokdarwis who are members of the community in the Sumber Jiput water area. After being provided with education on handling bleeding and first aid to drowning victims, an evaluation was conducted by asking questions to the participants. Increased knowledge was known when they were able to answer questions after the counseling activity. They are able to correctly describe drowning situations and the steps to take when encountering a drowning victim, as well as how to call for help. Furthermore, they can generally practice the steps in administering first aid to a drowning victim.